Impact of obesity with or without hypertension on systemic haemodynamic and renal responses to lower body negative pressure. (2nd January 2021) - Vakilzadeh, Nima; Petrovic, Dusan; Maillard, Marc; Favre, Lucie; Grouzmann, Eric; Wuerzner, Gregoire
Abstract: Purpose: Sodium and water handling by the kidney and the sympathetic nervous system have been implicated in the development of obesity-related hypertension and kidney disease. They have seldom been studied together during stress conditions. The objective of this study was to compare the systemic, renal and hormonal responses to lower body negative pressure (LBNP) in adult healthy participants (H), obese normotensive (OBN) and obese hypertensive patients (OBH). Materials and methods: This was a prospective case-control study. Participants from the three groups were exposed to one hour of LBNP. Systemic and renal haemodynamics, sodium and water excretion and hormones were measured before and after LBNP. Intergroup LBNP responses were tested using a Student t-test or a Wilcoxon rank-sum test. An extension of the Wilcoxon rank-sum test was used to test for a trend across the three groups. Results: The study included 54 participants (H: 25, OBN: 16, OBH: 13). LBNP induced a stepwise increase in systolic blood pressure (+2.7 ± 4.7 mmHg (H) vs. +4.7 ± 8.8 mmHg (OBN) vs. +8.0 ± 8.6 mmHg (OBH, p  = .028)) and heart rate (−1.3 ± 4.9 bpm (H) vs. 2.2 ± 6.1 bpm (OBN) vs. 1.9 ± 4.1 bpm (OBH, p  = .041). Urinary output (−2.8 ± 2.1 ml/min vs. −1.4 ± 1.7 ml/min, p  = .028) and free water clearance (−1.9 ± 1.7 mOsm/kg vs. −0.7 ± 1.3 mOsm/kg, p  = .016) responses were more marked in OBN compared to H. Conclusions: These results show that the systemic and the renal response to LBNP differ according to weight and to BP categories. Systolic BP and heart show a progressive increased response form healthy volunteers to OBN and then to obese hypertensive participants while urinary output and free water clearance responses are increased in OBN only, suggesting that the occurrence of hypertension in obese individuals modifies the early kidney responses to stress. ClinicalTrial.gov Identifier: NCT01734096